Comparative analysis of the prevention of caries by toothpastes with different compositions and their effect on the mineral structure of the oral fluid - E. V. Matveeva; I. N. Antonova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. One of the most attractive materials in the composition of toothpastes is hydroxyapatite with nanoscale crystals that contribute to the prolongation of remineralization due to the release of calcium and phosphorus. In some cases, macro- and micronutrients are introduced into preventive toothpastes; however, the dynamics of increasing their concentration in the oral fluid has not been studied enough.The objective was to study the effect of bioactive toothpaste with natural hydroxyapatite, enriched in nanodispersed particles of iron, zinc and copper, on the dynamics of the dental status and the level of copper, iron, zinc, magnesium and calcium in the oral fluid.Methods and materials. 26 patients were examined: 19 patients used the toothpaste being studied, and 7 patients used toothpaste, which did not have macro- and microelements. The determination of the Green-Vermilion hygiene index and the papillary-marginal-alveolar index was carried out, followed by calculation of the effectiveness of the cleansing and antiinflammatory effects. In the oral fluid, the method of electrothermal atomic absorption spectrometry was used for determination of the content of cations of copper, iron, zinc, magnesium and calcium.Results. One month after the start of the use of toothpaste with natural hydroxyapatites enriched with macro- and microelements, a statistically significant increase in the oral fluid of patient, levels of copper, iron, zinc and calcium was established. The effectiveness of the cleansing effect was 85 %, anti-inflammatory effectiveness – 90 %.Conclusion. The increase in the level of macro- and microelements in the oral fluid is due to the composition of the toothpaste containing, along with biogenic hydroxyapatite, nanodispersed particles of iron, zinc and copper.Authors declare no conflict of interest.The authors confirm that they respect the rights of the people participated in the study, including obtaining informed consent when it is necessary, and the rules of treatment of animals when they are used in the study. Author Guidelines contains the detailed information.